YTHDF1 in periaqueductal gray inhibitory neurons contributes to morphine withdrawal responses in mice - Ou, Chaopeng; Zhang, Kun; Mu, Yanyu; Huang, Zhenzhen; Li, Xile; Huang, Wan; Wang, Yan; Zeng, Weian; Ouyang, Handong (BMC medicine, 2024)
Physical symptoms and aversion induced by opioid withdrawal strongly affect the management of opioid addiction. YTH N6-methyladenosine (m A) RNA binding protein 1 (YTHDF1), an m A-binding protein, from the periaqueductal gray (PAG) reportedly contributes to morphine tolerance and hyperalgesia. However, the role of YTHDF1 in morphine withdrawal remains unclear. A naloxone-precipitated morphine withdrawal model was established in C57/BL6 mice or transgenic mice. YTHDF1 was knocked down via adeno-associated virus transfection. Combined with the results of the single-cell RNA sequencing analysis, the changes in morphine withdrawal somatic signs and conditioned place aversion (CPA) scores were compared when YTHDF1 originating from different neurons in the ventrolateral periaqueductal gray (vlPAG) was knocked down. We further explored the role of inflammatory factors and transcription factors related to inflammatory response in morphine withdrawal. Our results revealed that YTHDF1 expression was upregulated in the vlPAG of mice with morphine withdrawal and that the knockdown of vlPAG YTHDF1 attenuated morphine withdrawal-related somatic signs and aversion. The levels of NF-κB and p-NF-κB were reduced after the inhibition of YTHDF1 in the vlPAG. YTHDF1 from vlPAG inhibitory neurons, rather than excitatory neurons, facilitated morphine withdrawal responses. The inhibition of YTHDF1 in vlPAG somatostatin (Sst)-expressing neurons relieved somatic signs of morphine withdrawal and aversion, whereas the knockdown of YTHDF1 in cholecystokinin (Cck)-expressing or parvalbumin (PV)-expressing neurons did not change morphine withdrawal-induced responses. The activity of c-fos + neurons, the intensity of the calcium signal, the density of dendritic spines, and the frequency of mIPSCs in the vlPAG, which were increased in mice with morphine withdrawal, were decreased with the inhibition of YTHDF1 from vlPAG inhibitory neurons or Sst-expressing neurons. Knockdown of NF-κB in Sst-expressing neurons also alleviated morphine withdrawal-induced responses. YTHDF1 originating from Sst-expressing neurons in the vlPAG is crucial for the modulation of morphine withdrawal responses, and the underlying mechanism might be related to the regulation of the expression and phosphorylation of NF-κB.